Economic Empowerment of Indonesian Migrant Workers in South Korea Through Digital-Based Financial Literacy - Prajanti, Sucihatiningsih Dian Wisika; Bahatmaka, Aldias; Diantoro, Markus; Pujiarti, Herlin; Retnaningsih, Prihatini (Universitas Negeri Semarang, 2025)
Indonesian Migrant Workers (PMI) contribute significantly to the national economy through remittances, but still face challenges in managing their finances wisely. The low level of financial literacy and limited utilization of digital financial services cause many PMIs to have difficulties in long-term financial planning. This service program aims to empower Indonesian migrant workers in South Korea through digital-based financial literacy training using the Design Thinking approach. Five stages in this method: Empathize, Define, Ideate, Prototype, and Test, are used to design learning media that suits user needs. The results of the activity showed that the developed media, in the form of online modules, leaflets, and training videos, were rated as excellent by experts and migrant practitioners with an average score of 3.71 on a scale of 4. The evaluation also showed that this media is easy to understand, relevant to the needs of migrant workers, and has the potential to be developed sustainably. This service not only improves the financial literacy of migrant workers, but also opens up opportunities for program replication in other migrant communities.